2022
DOI: 10.4103/jfmpc.jfmpc_1367_21
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and attitude of young population toward CPR training, results from largest training session in an official attempt to enter Guinness Book of Records: A cross-sectional study from Saudi Arabia

Abstract: Objective: It has been proved that bystander cardiopulmonary resuscitation (CPR) saves lives and it is important to rise the willingness of the general population to help cardiac arrest victims. The primary objective of the present study is to assess the levels of the knowledge and attitude toward CPR among the young population who underwent the largest CPR training session in an official attempt to enter the Guinness Book of Records. Methods: Through a cross-sectional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 14 publications
0
1
0
1
Order By: Relevance
“…At the same time, regardless of the form chosen by the participants, it should be borne in mind that any of them may be beneficial even if they are dependent on the target group and technical, organizational, and financial capabilities [8,18,45]. A systematic review by Allan et al observed that innovative approaches, such as peer and self-based CPR training are equally effective as instructor-led methods when teaching schoolchildren [46].…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, regardless of the form chosen by the participants, it should be borne in mind that any of them may be beneficial even if they are dependent on the target group and technical, organizational, and financial capabilities [8,18,45]. A systematic review by Allan et al observed that innovative approaches, such as peer and self-based CPR training are equally effective as instructor-led methods when teaching schoolchildren [46].…”
Section: Discussionmentioning
confidence: 99%
“…Tindakan resusitasi jantung paru merupakan prosedur penting dalam mengahdapi korban henti jantung (Cheng et al, 2020). Keberhasilan dalam memberikan resusitasi jantung paru dapat menyelamatkan nyawa korban henti jantung (Gaafar, Khan, & Elmorsy, 2022).…”
Section: Gambar 7 Nilai Pre Test Dan Post Testunclassified